CONCRETE BRIDGE DESIGN PRT 80M SPAN TENSION - Muhammad Alif lutfi; Tony Hartono Bagio (NAROTAMA UNIVERSITY, Indonesia, 2023)
Kali warkapi bridge km 49+250 Manokwari, West papua which connects several districts in West papua province stretches 80m based because the bridge previously decreased until it is no longer feasible to use, the type of steel frame bridge structure, then in this final project the design for the replacement of kali warkapi bridge using prestressed concrete structure type at this initial stage the analysis of exsisting conditions, planning of upper and lower bridge structures and calculations is carried out. Superstructure planning takes into account the loads that may occur, namely self-load, additional dead load, traffic load, wind load and earthquake load. In planning the bridge is calculated using Ms.Excel.